Instalasi Mesin Generator Ozon dalam Meningkatkan Kualitas Sayur Organik di Desa Gedangan - Boyolali - Fanny Widadie; Nughtoh Arfawi Kurdhi; Lita Rahmasari (Universitas Sebelas Maret, 2023)
Installation of an Ozone Generator Machine to Improve the Quality of Organic Vegetables in Gedangan Village - Boyolali. The Utomo Jayan Farmers Group is an organic vegetable farmer group in Gedangan Village, Cepogo District, Boyolali Regency which has a major problem: the quality of vegetables. The vegetables produced by the group are quickly damaged, and many are returned by partners (buyers) due to needing to meet quality. The main purpose of this service activity is to assist in adopting post-harvest technology as an ozone generator to improve the quality of vegetables. Ozone technology can increase the shelf life of vegetables, prevent vegetables from spoiling quickly, reduce pesticide residues and harmful chemicals in the vegetables. The method of community service was conducted by socialization and active participation by involving all members of the farmer group. The results of this service activity were able to increase the shelf life of fresher vegetables within 20 days (red chilies), 14 days (tomatoes), 7 days (scallions), celery (9 days), and broccoli (5 days).